Strategy to Improve Courier & Logistics Performance in the Enterprise Business Directorate through the Influence of Price and Service Quality on Competitive Advantage: Empirical Evidence from PT Pos Indonesia (Persero) Regional 3 Bandung - Yogi Sudrajat; Saptono Kusdanu Waskito; Agus Purnomo (Dinasti Publisher, 2025)
The logistics and courier service sector plays an important role in supporting economic growth, especially in the era of digitalization and e-commerce expansion. PT Pos Indonesia, as one of the main players in this industry, faces challenges in improving the performance of couriers and logistics in Regional 3 Bandung. This study is important to understand the factors that influence company competitiveness in orders to improve efficiency and customer satisfaction. This study aims to analyze the effect of price and service quality on competitive advantage, and its impact on company performance at PT Pos Indonesia Regional 3 Bandung. The research method used is quantitative with a descriptive and verification approach. Data were collected through questionnaires from 182 PT Pos Indonesia customers and analyzed using SMART PLS to test the relationship between variables. The results of the study indicate that price and service quality have a significant effect on competitive advantage, which in turn has a positive impact on company performance. In addition, price and service quality also directly affect company performance. This study contributes to understanding strategies for increasing competitiveness in the logistics sector. The implication is that PT Pos Indonesia needs to adjust prices to the promised service standards and increase responsiveness to customer needs in order to improve competitiveness and business performance. Keyword: Price, Service Quality, Competitive Advantage, Company Performance, PT Pos Indonesia